SOVIET SLOGANS IN FICTION AND IN MODERN JOURNALISM AT THE END OF THE 20TH – THE BEGINNING OF THE 21ST CENTURIES - A. A. Osipova; S. G. Shulezhkova (Вестник Кемеровского государственного университета, 2015)
Soviet slogans act in different ways in social and political essays of different social movements of contemporaryRussiaand in works of one of the most prominent prose-writers of the 20th – the beginning of the 21st centuries, V.P Astafiev. Having revealed the peculiarities of propaganda political texts use, the authors carry out a comparative analysis which allows one to draw a conclusion about the role of language as the main tool of ideology. The slogans found in different media help to form journalistic store and attributes of social movements inRussiaat the end of the 20th – the beginning of the 21st centuries. In the long term, the authors are planning to compile a special dictionary. Particular attention is paid to the writer’s attitude to the political guidelines of the Communist Party of theUSSR. The role of Russian writers in anti-Soviet propaganda is analyzed, in particular, V. P. Astafiev’s contribution, who wanted to overthrow false ideas about the Great Patriotic war, imposed by the Soviet ideology. The authors of the article came to the conclusion that active introduction of an anti-Soviet and anti-Communist – which in fact is anti-Russian – stereotype into consciousness of Russians is dangerous as it leads to the destruction of the historical memory, causes chaos in the system of measuring and evaluation and prevents from the appropriate analysis of the past and from learning its lessons. The contemporary use of slogans connected with the Great Patriotic war allows us to realise that nowadays society is trying to revive lost ideals, to cultivate patriotism and civism.